Formation of Ni(II) Oxime-Bridged Basket-Like Complexes and their Structural Aspects - Holynska, Malgorzata (Current Inorganic Chemistry (Discontinued), 2015)
Two new Ni(II) complexes with phenyl 2-pyridyl ketoxime ligand are reported, displaying unprecedented basket-like topologies of their complex cores. The compounds are studied by X-ray diffraction, EDX and IR spectroscopy, confirming uncommon coordination of a DMF ligand in one of them.The reaction system is described in detail and some of the products are analyzed by EDX/SEM, including EDX mapping analyses of the elemental distribution.
Keywords: IR